PENERAPAN AUDIT OPERASIONAL DALAM UPAYA MENINGKATKAN EFISIENSI DAN EFEKTIVITAS FUNGSI PEMASARAN - Oktavia, Rizki Nanda; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The research is aimed to identify and to comprehend the application of operational audits in the assessment ofthe efficiency and the effectiveness of the marketing function. The data used is the primary and the secondarydata, this research object is PT KAI Daop VIII Surabaya. This research is descriptive research which is done byusing quantitative approach. Data collection techniques by using secondary data. The data analysis techniquehas been carried out by performing observation, interviews and documentation. The result of the analysis andthe problem is the implementation of operational audits in the marketing function experiences disruption inrunning online ticket sales which is constrained by unstable internet network and online sales available but itdoes not serve the local economy-class train ticket. It can be concluded from the result that the cause ofinefficiency and ineffectiveness in the marketing function can be found by using operational audit, i.e.: bookingfactor for economic class local train ticket which can not be accessed by online and maintenance factor in theinternet network that suddenly have trouble. In the process of online ticket sales, the internet which has beenused by the company should be improved in order to overcome the inefficiency and the ineffectiveness in themarketing function.Keywords: operational audit, effectiveness, efficiency, marketing functions